Age and gender characteristics of dyslipidemia prevalence among the Bishkek city residents - T. M. Murataliev; V. K. Zventsovа; Z. T. Radzhapova; I. V. Kalinicheva; N. Zh. Zhanyshbekova; u. E. Sultan; S. Yu. Mukhtarenko (Klinicist)
Materials and methods. The results of lipid profile cross-sectional study of 2088 Bishkek residents aged 18—65 years who came to “Bonetsky Laboratory” from January to December 2016 were analyzed.Results. Among 2088examined residents there were 938 (44.9 %) men and 1150 (55.1 %) women; 48.4 % of them had an increased level of total cholesterol (≥5.2 mmol / l). The prevalence of hypercholesterolemia (HC) in women was higher (52.3 %) than in men (43.6 %). With age in both men and women, the increased frequency of HC was found, in men the peak was observed at the age of50—59years (50.3 %), and in women >60 years (61.2 %). HC associated with lipoprotein content (low-density lipoprotein >2.58 mmol/l) was found in 80.0 %, and in women more often than in men (81.6 and 78.1 % respectively). In both male and female, the greatest rise in HC dynamics was observed at the age of30—39years, then a monotonous rise of HCfrequency was observed in women (86.0 %) >60years, and in men the subsequent rise of HC from the age of 30—39 years was not observed. Reduced levels of high density lipoproteins up to 30 years of age were more common in women than in men (46.4 % vs 29.0 %). The peak in the frequency of low level of high density lipoproteins was found at the age of40—49years and was more often in women. Hypertriglyceridemia (>1.7 mmol/l) up to 30 years of age was registered with the same frequency regardless of gender and age (36.0 % in women, 37.0 % in men). Two-factor variance analysis for the lipid profile showed a high statistical significance of gender and age.Conclusion. The study showed a high prevalence of dyslipidemia among the population of Bishkek city. The presented data justify the necessity of active prophylaxis for primary and secondary prevention of ischemic heart disease among the population.